2019
DOI: 10.3390/cells8030235
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Landscape of Cisplatin-Resistant Neuroblastoma Cells

Abstract: The efficiency of cisplatin (CDDP) is significantly hindered by the development of resistance during the treatment course. To gain a detailed understanding of the molecular mechanisms underlying the development of cisplatin resistance, we comparatively analyzed established a CDDP-resistant neuroblastoma cell line (UKF-NB-4CDDP) and its susceptible parental cells (UKF-NB-4). We verified increased chemoresistance of UKF-NB-4CDDP cells by analyzing the viability, induction of apoptosis and clonal efficiency. To s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 56 publications
1
18
1
Order By: Relevance
“…In addition, the up-regulation of ATP-binding cassette transporters (ABC family members) provides a supporting mechanism for direct efflux of CDDP from the cell via energy-fuelled active transport. CDDP can further activate the proteasome complex pathway, which was also demonstrated by our previous results 24 , 46 . Interestingly, we also identified a pronounced up-regulation of numerous proteasome subunits in UKF-NB-4 cells overexpressing hMT3.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, the up-regulation of ATP-binding cassette transporters (ABC family members) provides a supporting mechanism for direct efflux of CDDP from the cell via energy-fuelled active transport. CDDP can further activate the proteasome complex pathway, which was also demonstrated by our previous results 24 , 46 . Interestingly, we also identified a pronounced up-regulation of numerous proteasome subunits in UKF-NB-4 cells overexpressing hMT3.…”
Section: Discussionsupporting
confidence: 86%
“…CDDP is a cytotoxic drug that kills cancer cells by damaging DNA and inhibiting its synthesis 22 , 23 . Despite the high efficiency of CDDP, cancer cells frequently develop a CDDP-chemoresistance phenotype, which could be due to a wide spectrum of causes, including decreased blood flow into tumour mass, inhibited internalization of CDDP, exocytosis of CDDP, intracellular sequestration of CDDP, halted DNA repair or apoptosis-driving mechanisms, or a presence of quiescent and non-cycling cells (non-growing or non-dividing state for a long period of time) 24 . As shown in our previous transcriptomic study, up-regulation of hMT3 induced development of CDDP-chemoresistance in Nbl cells and significantly altered the expression of sets of genes involved in apoptosis and oncogene-induced senescence 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, utilizing cell lines as models mechanisms mediated through intra-tumoral oncogenes, mutations and signaling cascades, as well as extra-tumoral factors, such as stromal components and non-cellular components, have been identified to affect CDDP sensitivity [ 10 , 14 , 15 , 16 , 17 ]. Multiple mechanisms mediated by oncogenes, such as exosomal-microRNAs and cell signaling pathways, were identified to promote CDDP-insensitivity in neuroblastoma [ 10 , 18 , 19 , 20 ]. The oncogenes, including v-myc avian myelocytomatosis viral oncogene neuroblastoma derived homolog (MYCN) and Hypoxia-inducible factor (HIF)-1∝, were shown to regulate metabolism and mediate CDDP-resistance in neuroblastoma [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of a role for MT-3 in lysosomal function, the absence of MT-3 results in changes in the levels of lysosomal proteins and results in reduced lysosomal degradative capacity. Lee et al, proposed that MTs might similarly stabilize lysosomes following autophagocytotic delivery to the lysosomal compartment [ 86 ]. Also, Cho et al demonstrated the roles of MT-3 and zinc in radiation-induced autophagy and radio-resistance in glioma cells [ 87 ].…”
Section: Metallothioneins Regulates Lysosomal Function In Cancer Cmentioning
confidence: 99%